Effect of a hyper deformation drawing process on mechanical behaviour of thin wires of Ti-26Nb (at.%) alloys. (15th April 2017) - Gabrion, Xavier; Thibaud, Sébastien; Zang, Yudong; Charbonnier, Pierre; Laheurte, Pascal; Gaillard, Yves
Abstract: This paper investigates the mechanical properties of hyper deformed wires of Ti-26 at.%Nb (Ti-26Nb) alloy that can be equally expressed as Ti-40.5 wt.%Nb. These wires obtained by hot drawing process have a diameter of 85 μm and 285 μm, respectively. The effect of a short heat treatment at 748 K for 600 s was also investigated. The influence of the heat treatment and the diameter of the wires evaluated by mechanical tests, such as nano indentation, quasi-static tensile, and fatigue tests, and microstructure investigations. The quasi-static tensile tests show that the mechanical properties, like elasticity modulus and ultimate tensile strength, are improved with the decrease of the diameter. An increase of 55% and 26% in strength is obtained for the non-treated state and the heat treated state, respectively. The improvements in the mechanical properties for the 285 μm diameter wire are due to the refinement of grains to submicron scale between 100 and 200 nm. The short heat treatment induces an increase of the Young's modulus and a decrease of the ultimate tensile strength by the emergence of a dual phase ( α and β ) microstructure. For fatigue tests, the increase of frequency from 4Hz to 30Hz leads to an increase of 45% of the fatigue life time. Graphical abstract: Highlights: The tensile and fatigue properties of Ti-26Nb (at.%) alloy thin wire are investigated by different tests. The grain size at submicron scale (100 to 200 nm) leads to an increase of strength. The short heat treatment at 748 K for 600 s induces a dual phase ( α  +  β ) in the material. The fatigue life time is more important with increasing the solicitation frequency.